Correction: Multi Locus Variable-Number Tandem Repeat (MLVA) Typing Tools Improved the Surveillance of Salmonella Enteritidis: A 6 Years Retrospective Study. - Sophie Bertrand; Guillaume De Lamine de Bex; Christa Wildemauwe; Octavie Lunguya; Marie France Phoba; Benedikt Ley; Jan Jacobs; Raymond Vanhoof; Wesley Mattheus (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0117950.].